Sourcebook of Family Theories and Methods
XXVI, 748 p.
Keywords: Now in softcover, the Sourcebook of Family Theories and Methods distills nearly a century of theories and therapies into one comprehensive volume. This unique sociohistorical account of family studies traces the development of various theories and methods within the sociopolitical context of the twentieth century, giving readers a practical balance of scientific and real-world perspective. Contributors review each theory and method in terms of its origins, core assumptions, applications, and links to previous and successive theories and methods. Specific chapters provide in-depth applications with couples, families, step and blended families, minorities, families with histories of violence, and families facing chronic illness, as well as potential uses in policy, education, or further research. In this way, readers may find new ideas and possibilities in older or less familiar schools of thought. At the same time, the book offers the foundation for the future of the field. A sampling of the coverage: Systems theory. Human ecology theory. Life course perspectives. Social-cognitive-behavioral theory. Feminist theory. Theories derived from family therapy. Biosocial theory. Ethnomethodology. A historical reference that doubles as a contemporary idea book, the Sourcebook of Family Theories and Methods belongs in the libraries of family therapists and psychologists, social workers, and sociologists specializing in families. Policy analysts in this critical area should find the Sourcebook significant reading as well.